Community Behavior and the Exposure of River in Yogyakarta from Feses Coli Bacteria (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
This study started from data of Riskesdas of the Ministry of Health which regards Special Region of Yogyakarta as a region with a good habit of defecating. However, according to a research conducted by the Environment Agency in Yogyakarta, all rivers in this region contain faecal colibacteria far above the threshold. This study aims to explain the factors that led to contamination of rivers by faecal colibacteria in Yogyakarta. The researcher conducted observation in the rivers in Yogyakarta and interviewed some people who lived near the rivers regarding their habit and knowledge about the riversâ€™ condition. This study concluded that the habit of defecating in rivers is rarely found in Yogyakarta and such habit will diminish naturally. However, there are some behaviors which give similar effects as defecating in rivers.Â The society does not know that such behaviors could lead to the presence of faecal colibacteria. More importantly, although the rivers in Yogyakarta contain faecal colibacteria which UNICEF considers as harmful, the society does not confirm that such condition is harmful. This way, such unhealthy behavior of the society still exists.